Effect of anti-vascular endothelial growth factor on the surgical outcome of neovascular glaucoma: An overview and meta-analysis. Issue 39 (1st October 2021) - Hwang, Hyung Bin; Lee, Na Young
Abstract: Background: Bevacizumab is known to be very effective in inhibiting ocular neovascularization in neovascular glaucoma (NVG). The purpose of this study is to evaluate the effect of anti-vascular endothelial growth factor on the surgical outcome of Ahmed glaucoma valve implantation (AGVI) in NVG. Methods: An extensive search of PubMed, EMBASE, and the Cochrane Library was carried out in January 2021 to select relevant studies. The weighted mean difference of the intraocular pressure reduction percentage from baseline to endpoint was used for the primary efficacy estimate. Mantel–Haenszel odds ratios and 95% confidence intervals (CIs) for success rate were employed as secondary efficacy estimates. The number of postoperative interventions and the tolerability estimate for adverse events were also measured using odds ratios. We conducted meta-analyses of fixed effects models using comprehensive meta-analysis software to pool the results of the included studies. Heterogeneity was assessed using Q-value and I 2 measures. Results: Nine studies were included in the analysis, encompassing a total of 410 eyes. There was no significant difference in intraocular pressure reduction percentage between the AGVI-only group and the AGVI with adjuvant bevacizumab group (estimate 0.324; 95% CI, −0.278-0.926; P = .244). However, the success rate favored the AGVI with adjuvant bevacizumab group (estimate 0.561; 95% CI, 0.097-1.025, P = .018). Conclusions: AGVI with adjuvant bevacizumab had no significant effect on lowering IOP in patients with neovascular glaucoma compared with AGVI alone. However, the final success rate was higher for AGVI with adjuvant bevacizumab treatment than with AGVI alone.